Labour cost in Italy and the E.E.C. countries - VANNUTELLI, C. (PSL Quarterly Review, 2014)
The European Community Statistical Institute (ECSI) began conducting annual surveys of labour costs in 14 industrial sectors of the Community countries in 1959. The present article illustrates the principal results of the fourth survey that relates to 1962 and is now in course of publication. The analysis is confined to data regarding to labour cost shown as borne by the enterprises, and does not take account of studies made by ECSI of workers’ incomes in various countries. In particular, the author considers the data on the cost of labour in Italy. The data is brought up to date for 1963 and 1964 to show the changes that have taken place in Italy’s position with respect to previous years. While in the surveys tom 1959 and 1960 Italy was shown to have the lowest labour cost among Common Market countries, it now comes in first in the classification and has in almost every case registered a labour cost very near to the highest figure. JEL: E24, J30